ANALISIS PENGARUH PAJAK HOTEL DAN RESTORAN TERHADAP PERTUMBUHAN EKONOMI KOTA BATU: PENDAPATAN ASLI DAERAH SEBAGAI FAKTOR INTERVENING: Pajak Hotel, Pajak Restoran, Pendapatan Asli Daerah, Pertumbuhan Ekonomi - Ekasari, Luh Dina; Indah, Sri; Susanti, Rizki Aprilia Dwi; Hayuningtyas, Ruri Fitria (Jurnal Paradigma Ekonomika, 2024)
The purpose of the study was to determine the effect of hotel and restaurant taxes on economic growth with the mediation of local revenue. In an autonomous region or region that has the power to manage its area, it is strived to get potential results, which requires policies to increase economic growth in a region. In increasing economic growth, hotel and restaurant taxes also influence the increase in economic growth also influenced by hotel and restaurant taxes. This provides evidence of the many tourists from various foreign and local tourists who often come to Batu City. From this there must be an effort to increase economic growth in Batu City needs to get good attention and the local government is obliged to optimize its tax collection, especially in the hotel and restaurant tax sector in the Batu City local government area. In this study using secondary using path analysis techniques using the Smart-PLS program with a quantitative approach. From the results of the analysis directly shows that hotel tax and restaurant tax affect local revenue partially and hotel tax also affects economic growth while restaurant tax has no effect on economic growth. In indirect research, local revenue is not able to mediate the hotel tax.